Perubahan hematologi pada sapi dengan theileriosis tropis: tinjauan sistematis - Akbar Wicaksono (Fakultas Pertanian Universitas Majalengka, 2026)
Bovine tropical theileriosis, caused by Theileria annulata, is an important tick-borne disease in cattle that is frequently associated with clinically relevant hematological disturbances. This systematic literature review aimed to synthesize published evidence on hematologic alterations reported in cattle affected by bovine tropical theileriosis, with an emphasis on erythrogram, leukogram, and platelet-related changes. The review question was structured using the PEO format: cattle infected with T. annulata as the population, bovine tropical theileriosis as the exposure, and hematologic alterations as the outcome. Literature screening was conducted using a Scopus-led search and complementary source verification with predefined inclusion/exclusion criteria. Original research articles involving cattle with confirmed T. annulata infection and reporting at least one hematological parameter were included in this review. Review articles, buffalo-only studies, mixed-species reports without separable cattle data, and papers lacking extractable hematologic outcomes were excluded from the study. The current synthesis showed that the most consistent alterations were decreases in red blood cell count, hemoglobin concentration, and packed cell volume/hematocrit, indicating that anemia is the dominant hematologic feature of bovine tropical theileriosis. In contrast, leukogram findings were more heterogeneous, with studies reporting leukopenia, leukocytosis, lymphocytopenia, lymphocytosis, neutropenia, or mixed patterns, depending on the disease severity and study context. Platelet-related abnormalities were less frequently reported but generally suggested thrombocytopenia in severe clinical cases. Overall, erythrogram alterations were the most consistent hematologic indicators of cattle infected with T. annulata.